2021
DOI: 10.3389/fncom.2021.738885
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Cerebral Microbleed Detection via Convolutional Neural Network and Extreme Learning Machine

Abstract: Aim: Cerebral microbleeds (CMBs) are small round dots distributed over the brain which contribute to stroke, dementia, and death. The early diagnosis is significant for the treatment.Method: In this paper, a new CMB detection approach was put forward for brain magnetic resonance images. We leveraged a sliding window to obtain training and testing samples from input brain images. Then, a 13-layer convolutional neural network (CNN) was designed and trained. Finally, we proposed to utilize an extreme learning mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In this study, five out of 9 patients with severe HACE who underwent SWI scans showed CMBs, which were significant in the corpus callosum, and one patient with diffuse CMBs died. Some studies suggest that CMBs can lead to cognitive dysfunction and increase the risk of stroke ( 28 , 33 ) and even death ( 37 ). Therefore, we believe that patients developing CMBs often have poor prognoses and should be treated promptly.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, five out of 9 patients with severe HACE who underwent SWI scans showed CMBs, which were significant in the corpus callosum, and one patient with diffuse CMBs died. Some studies suggest that CMBs can lead to cognitive dysfunction and increase the risk of stroke ( 28 , 33 ) and even death ( 37 ). Therefore, we believe that patients developing CMBs often have poor prognoses and should be treated promptly.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are convolutional neural networks (CNN) [168], which are the most popular solution [22,53,78,77,23,124,75,49,72].…”
Section: Neural Network-based Methodsmentioning
confidence: 99%
“…It might be performed using the sliding neighborhood processing (SNP) technique to produce smaller fragments of the original image. A lot of works utilized this method: [46,22,53,48,47,52,139,4,14,77,23,124,125,75,49].…”
Section: Pre-processingmentioning
confidence: 99%
“…It consists of input layer, hidden layer and output layer [30]. Each layer consists of several neurons, each neuron receives the output of the previous layer as input, and then generates output to the next layer [31], which belongs to one-way propagation [32]. According to the number of hidden layers, it is divided into single-layer feedforward neural network and multi-layer feed-forward neural network.…”
Section: Extreme Learning Machinementioning
confidence: 99%